NET PROFIT MARGIN IN MEASURING PROFITABILITY IN PERUMDA PASAR CHAMPION BANDUNG - Juwita Aprillia; Abdul Manap; Nuuridha Matiin; Nurlia Nurlia; Jean Richard Roku (Jurnal Ekonomi, 2023)
This study aims to determine the effect of Net Profit Margin in measuring the Profitability of Perumda Pasar Juara. The population used in this study is the financial statements of Perumda Pasar Juara for the 3 year period 2019-2021. The income statement and balance sheet of Perumda Pasar Juara are used as research samples. The technique of determining the sample using purposive sampling. This type of research is a quantitative method utilizing a descriptive approach. The research data were analyzed through linear regression analysis using SPSS 26. The results of this study were that the net profit margin had a positive and significant effect on measuring the profitability of Perumda Pasar Juara.